A 12-pulse rectifier with passive harmonic reduction based on UIPT in more electric aircrafts. Issue 2 (8th March 2021) - Abdollahi, Rohollah
Abstract : Purpose: The purpose of this paper is to provide a T autotransformer based 12-pulse rectifier with passive harmonic reduction in more electric aircraft applications. The T autotransformer uses only two main windings which result in volume, space, size, weight and cost savings. Also, the proposed unconventional inter-phase transformer (UIPT) with a lower kVA rating (about 2.6% of the load power) compared to the conventional inter-phase transformer results in a more harmonic reduction. Design/methodology/approach: To increase rating and reduce the cost and complexity of a multi-pulse rectifier, it is well known that the pulse number must be increased. In some practical cases, a 12-pulse rectifier (12PR) is suggested as a good solution considering its simple structure and low weight. But the 12PR cannot technically meet the standards of harmonic distortion requirements for some industrial applications, and therefore, they must be used with output filters. In this paper, a 12PR is suggested, which consists of a T autotransformer 12PR and a passive harmonic reduction (PHR) based on the UIPT at direct current (DC) link. Findings: To show the advantage of this new combination over other solutions, simulation results are used, and then, a prototype is implemented to evaluate and verify the simulation results. The simulation and experimental test results show that the input current total harmonic distortion (THD) of the suggested 12PR with a PHR based on UIPT is less than 5%, which meets the IEEE 519 requirements. Also, it is shown that in comparison with other solutions, it is cost effective, and at the same time, its power factor is near unity, and its rating is 29.92% of the load rating. Therefore, it is obvious that the proposed rectifier is a practical solution for more electric aircrafts. Originality/value: The contributions of this paper are summarized as follows. The suggested design uses a retrofit T autotransformer, which meets all technical constraints, and in comparison, with other options, has less rating, weight, volume and cost. In the suggested rectifier, a PHR based on UIPT at its dc link of 12PR is used, which has good technical capabilities and lower ratings. In the PHR based on UIPT, an IPT is used, which has an additional secondary winding and four diodes. This solution leads to a reduction in input current THD and conduction losses of diodes. In full load conditions, the input line current THD and power factor are 4% and 0.99, respectively. The THD is less than 5%, which satisfies IEEE-519 and DO-160G requirements.